PID controller optimized by Big Bang-Big Crunch algorithm for the evolution of router bandwidth demand - Giannopoulos, Iordanis K.; Leros, Asimakis K.; Leros, Apostolos P.; Kofinas, Panagiotis; Dounis, Anastasios I. (International journal of information technology (Singapore. Online), 2020)
This paper presents an application of the Big Bang-Big Crunch algorithm to estimate with high precision the gains Kp, Ki and Kd of a PID controller. The optimized PID controller together with an evolution model is useful for the network administrators as it provides information within 5 or 15-min intervals for the bandwidth distribution. Furthermore, the Big Bang-Big Crunch algorithm results will be compared with those computed by the analysis of a classical PID controller. Finally, simulations with Simulink package are presented to compare the two methodologies.